Insights into body composition adaptation: should we reconsider the use of Body Mass Index in some sports? - Durmic, T.; Djelic, M.; Suzic Lazic, J.; Lazovic Popovic, B.; Dekleva, M.; Soldatovic, I.; Mazic, S. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purposes of this study were to indentify the under/overweight/obese frequencies by Body Mass Index (BMI) and body fat percentage (BF%) in athletes within groups of sport and to investigate the accuracy of the BMI as a measure of BF%.